Paradoxes of Press Freedom in Colonial West Africa. Issue 1 (2nd January 2016) - Newell, Stephanie
Abstract : This article describes the shifts and contradictions in British approaches to the control of print media in colonial West Africa between the 1920s and 1940s. Well before the Colonial Office's post-war interventions to create an 'enlightened and educated' West African citizenry through mass education, decades of independent newspaper production in the region helped to shape independent and critical readerships. For the British, however, an upsurge in African nationalist journalism in the mid-1930s coincided with a perceived Communist infiltration of 'British West Africa' to make censorship and surveillance more palatable than before to colonial officials in London, in spite of the new emphasis on public relations.